Diabetes-Induced Tyrosine Nitration Impairs Glutamine Synthetase Activity and Exacerbates Neurotoxicity in a Rat Model. Issue 1 (2018) - Matragoon, Suraporn; MS, MS; El-Remessy, Azza B
No abstract available